A CRITICAL REVIEW OF THE SC/ST ACT’S PERFORMANCE IN PREVENTING ATROCITIES AGAINST MARGINALIZED COMMUNITIES - Tamgadge, Sandeep Madhukar; Khobragade, Pravina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India made a huge stride toward social fairness with the PoA Act of 1989. It was designed to stop caste violence and systemic discrimination that have been going on for a long time, providing people who are on the outside more safety and access to justice. However, more than thirty years later, a closer look at how it was put into operation shows that there are still huge holes. These problems not only make it difficult for the Act to prohibit bad things from happening, but they also make it less likely that it will bring about justice fast. This examination focuses on two main aspects of how the Act works: problems with implementation and how well the courts work. The purpose of items like special courts and exclusive processes was to speed up the process of getting justice. But in real life, their power has been limited by factors like insufficient infrastructure, long delays to file a FIR, poor police investigations, and not enough aid for victims to get better. The courts’ decisions are analogous to these problems. The conviction rate is still low because witnesses are not willing to help, the evidence is weak, and the system is not operating right. In 2018, the Supreme Court weakened arrest rules, which made victims feel less protected. In 2019, the rules were put back in place. Some states have much greater conviction rates and case backlogs than others, which suggests that the courts don’t always care for the Act’s intentions. For survivors, getting justice often means fighting with a system that is unjust and works against them. A lot of individuals don’t file or keep complaints because the police are hesitant, witnesses don’t feel safe enough, and the procedure takes too long. The Supreme Court has occasionally stepped in to find a middle ground between protecting rights and eliminating abuse. However, these moves have also made it tougher to put things into effect on the ground. The best thing to do is make adjustments to the structure. This includes stronger means to protect victims and witnesses, strict timelines for trials, training for judges and police on how to be sensitive, and regular inspections on special courts. Most crucially, reforms need to go beyond correcting things one at a time. Instead, they need to be based on a plan that involves changes to the law, the courts, and the government. After that, the Act can only grow closer to keeping its promise in the Constitution to protect the rights of groups who have historically been victims of violence and discrimination.